(untitled) (ModaPalavra e-periódico, 2021)
This article aims to discuss the relationship between fashion and the media and their influence on people’s consumption actions. It aims to show that consumption trends are used by companies to endorse the process of buying a product. Such trends represent the inclinations of consumers and may indicate future changes in the consumption of products. The methodology used was a bibliographic study of how the development of the media, particularly television, in Brazil and also an analysis of two advertising campaigns with two different celebrities in order to understand how the endorsement was used by the company. It was realized that using celebrities or digital influencers is a marketing strategy that is effective when it comes to presenting or selling a product, as long as that celebrity has empathy and affinity with what is disclosed.